Scoping report: Integrated Farming System Models across food, land and water systems - Shamim, M.; Ravisankar, N.; Ansari, M.A.; Prusty, A.K.; Singh, Raghuveer; Raghavendra, K.J.; Kumar, Sunil; Jain, Namrata; Borah, Gulshan; Kumar, Gopal; Malaiappan, Sudharsan; Sikka, Alok (2024)
In response to the urgent need for climate-resilient agricultural practices, Integrated Farming Systems (IFS), Organic Farming Systems (OFS), and Natural Farming Systems (NFS) have emerged as key strategies for promoting sustainable agriculture. These approaches offer holistic solutions that address the adverse impacts of climate change while enhancing resilience and restoring ecological balance within agricultural landscapes. Each of these systems underscores the complex relationships between human activities, natural ecosystems, and climate patterns, making them essential in the shift toward sustainable and regenerative agriculture. This report highlights the importance of Transformational Agroecology—a comprehensive approach that spans food, land, and water systems—to create sustainable, resilient, and equitable food systems capable of withstanding the growing challenges of climate change, biodiversity loss, and food insecurity. By implementing agroecological principles, we can foster an inclusive, regenerative agricultural system that benefits both people and the planet. While some farmers are already practicing integrated farming systems, these efforts are often not systematically planned or optimized for resource efficiency, despite their inherent agroecological value. To enhance the resource efficiency and ecological sustainability of these practices, the ICAR-Indian Institute of Farming Systems Research (ICAR-IIFSR) conducted a scoping study in the Narayanganj block of Mandla district, Madhya Pradesh. This study aims to refine integrated farming methods, aligning them more closely with agroecological principles to ensure a sustainable and resilient agricultural framework that meets the evolving environmental and socioeconomic demands.